How can the priorities of older, frail patients and their carers be used to inform policy and practice at the end of life? Insights from qualitative research across multiple settings. Issue 3 (21st March 2023) - Barker, Rhiannon Jane; Wilson, Patricia; Butler, Claire
Abstract : Objectives: The paper reports on experiences from older patients and their carers of current provision of end-of-life care in England. It draws on data from a study that sought to explore the extent to which national policy for end-of-life care in England was aligned with the aspirations of stakeholders. Specifically, the study explored the balance between clinical healthcare vs social and relational care asking how this was aligned to patient priorities at this time of life. Here, we examine the extent to which the patient voice is attended to when health and social care services are delivered to older people and consider how the experiences of patients and carers could be used to improve outcomes. Design: The work draws on data collected as part of a realist informed study using a case study approach to gather data. Setting: Clinical Commissioning Groups were used as the boundaries of the three case studies and within these geographical areas data was collected in hospitals, care homes, hospices and patient homes. Participants: This paper reports on in-depth interviews conducted with 21 patients at the end of life and 22 relatives/carers (n=43). Results: While the medical care patients received was generally praised, it was reported that relational care, particularly in respect to adult social care received at home, was fragmented and of varying quality. Relational and social support were key to the patient and carer experience yet appeared to be hard to access. Conclusion: The work highlights the misalignment between the availability of different types of care at the end of life and patient priorities. More attention should be paid to the voice of older patients and their carers, drawing on their experiences to influence the way policy is translated into practice.